Feed specially used for raising chickens - CUI YINGXUE (2018)
The invention discloses feed specially used for raising chickens. The feed is prepared from the following raw material components in parts by weight: 20-30 parts of corn, 25-35 parts of soybeans, 20-30 parts of peanut shell, 5-10 parts of chestnut shell, 5-10 parts of walnut shell, 1-2 parts of calcium hydrogen phosphate, 0.1-0.5 part of zinc oxide, 0.1-0.5 part of vitamin E, 1-5 parts of lemon grass, 0.5-1 part of rush pith, 0.1-0.3 part of table salt and 2-8 parts of edible oil. The feed provided by the invention is rich in trace elements needed by the growth of the chickens, can acceleratethe growth speed of the chickens, does not contain hormone substances, and is green, safe and free from pollution. 本发明公开了种养鸡专用饲料，其原材料按照重量份数包含如下组分：玉米20-30份、大豆25-35份、花生壳20-30份、板栗壳5-10份、核桃壳5-10份、磷酸氢钙1-2份、氧化锌0.1-0.5份、维生素E0.1-0.5份、柠檬草1-5份、灯心草0.5-1份、食盐0.1-0.3份、食用油2-8份。本发明富含鸡生长所需的微量元素，可以加快鸡的生长速度，不含有激素类物质，绿色安全，无污染。